Sistemas e épocas de cultivo na produção agronômica e de óleo essencial de Melissa officinalis L. - Silva, Sérgio Macedo (2011)
Melissa officinalis is a medicinal and aromatical, species originary from Asia and Europe, adapted to a subtropical and tempered climate, being, however, found in almost all Brazil. To discover which they are the forms to get one high productivity and products with the essential oil concentrations and good quality and amount it is necessary to submit to the plants the most different conditions, between them: growing season (spring-summer and autumn-winter), ontogenetics interval of cut, periods of training (phases that possess oil concentration better), climatic density of plantation, prunings, conditions, forms of culture, as greenhouse and field. The objective of this work was to submit plants of lemon balm at the same time to two types of fertilization, two systems of culture at two distinct times (spring/summer and autumn/winter), in the conditions of Uberlândia, MG, Brazil, to evaluate the vegetal production and of essential oil. The experiment was lead in field and greenhouse in the Experimental Farm of the Glory, pertaining to the Federal University of Uberlândia (UFU). Two experiments at two distinct times had been carried through, characterized as spring/summer and autumn/winter. The first experiment occurred enters the months of October of 2009 and February of 2010 and as it enters the months of May and August of 2010. The used experimental delineation in the two experiments was of casualised blocks (DBC), in factorial project 2 x 2, with five repetitions, being two systems of culture (greenhouse and field) and two types of fertilization (mineral and organic). Height of the plant, length and foliar width, cool mass had been evaluated and dry, essential oil text, income and composition. The time spring/summer and the culture in the greenhouse had provided the best conditions for the good development of lemon balm. The average greaters of height had been found in the greenhouse using the organic fertilization at the two times of study. The fertilization did not intervene with the essential oil income of lemon balm for time spring/summer. The production of biomass of lemon balm was considerably bigger at the time spring/summer in relation the autumn/winter, as well as in the greenhouse in relation to the field at the two times. The chemical composition of the oil was similar for the plants cultivated in protecting environment and field, for cool mass and dry mass, taking advantage as constituent majority the neral, the geranial and the citronelal at the two times of study. The time autumn/winter in such a way did not favor the production of the majority constituent (neral and geranial) as in the spring/summer. The biggest availability of nutrients for the organic fertilization, associate to the increase of the humidity of the ground, allowed to the increase of the fotoassimilates biomass and the translocations of for the secondary metabolism in the plants of lemon balm.